2018
DOI: 10.1111/jace.15741
|View full text |Cite
|
Sign up to set email alerts
|

De‐densification mechanisms of yttria‐doped cerium oxide during sintering in a reducing atmosphere

Abstract: The presence of residual carbon in oxides in which the valence state can change during sintering may lead to de‐densification or swelling phenomena during the last stage of sintering. This was demonstrated by sintering a Ce0.85Y0.15O2‐x powder compact with or without added graphite carbon in a reducing atmosphere (Ar/5 vol.% H2) at 1450°C. The shrinkage behavior was studied with a dilatometer combined with an oxygen probe and a gas chromatograph to analyze the composition of the released gases. Oxide reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The presence of impurities coming from the hydrothermal degradation of U(C2O4)2.nH2O was finally checked in the oxide samples. Indeed, previous works showed that the presence of residual carbon in the oxide powders could impact negatively the densification step 9,11,12 . Powders were then first characterized thanks to a carbon analyzer ( 9 .…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The presence of impurities coming from the hydrothermal degradation of U(C2O4)2.nH2O was finally checked in the oxide samples. Indeed, previous works showed that the presence of residual carbon in the oxide powders could impact negatively the densification step 9,11,12 . Powders were then first characterized thanks to a carbon analyzer ( 9 .…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…This difference can be explained by the presence of smaller crystallites which react more quickly to sintering [19]. Above 1500°C, a phenomenon of de-densification, sometimes called "solarisation", was also observed, which could have been be caused by coalescence of pores or exaggerated grain growth [15], [25]- [28]. 1).…”
Section: Dilatometric Studymentioning
confidence: 99%
“…This morphological feature can limit the powder flowability when shaping pellets for ceramic fabrication, and then induce some mechanical defects after sintering. Also, oxide based powders coming from oxalate precursors generally incorporate residual traces of carbon, typically from around 100 ppm when calcined under air [13] up to several thousands of ppm for thermal conversion performed under inert or reducing atmosphere [12], which have been associated to dedensification processes [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth noting that a slight weight loss signal was recorded between 500 and 1000°C, and associated with the detection of small amounts of CO and CO 2 , which could be assigned to the elimination of residual carbon in the sample. Indeed, the thermal decomposition of MO 2 precursors, including carboxylates such as oxalates, was systematically associated with the presence of amorphous carbon within the final oxides 39,40 .…”
Section: Thermal Behaviour Of Uo 2 Particlesmentioning
confidence: 99%